The synergetic effects of the surface wettability and the patterned nanostructure on boiling heat transfer enhancement. (September 2021) - Xie, Shangzhen; Ma, Xiaoxia; Kong, Haojie; Bai, Songnan; Jiang, Mengnan; Zhao, Jiyun
Highlights: The nanofilms coated on the surfaces show superior CHF and HTCmax than the plain surfaces. The pattern boundaries contribute the boiling curves shifting left and optimize the nucleation sites into regular pattern on the patterned surface other than random sites on the plain or fully structured surfaces for the bubble development. The surface with thermo-responsive wettability demonstrated the superiority in enhancing the CHFs. Abstract: Engineering nano-structured surfaces with mixed/thermo-responsive wettability offer a new approach to improve the boiling performances of advanced thermal systems, such as the solar system and the heat dissipation systems in nuclear power plants, where more efficient cooling and higher safety limits are extremely desirable. In this study, five groups of surfaces: a) plain surfaces, b) nanofilm coated surfaces, c) patterned surfaces with superhydrophilic nanograss, d) patterned surfaces with superhydrophobic nanograss, f) patterned surfaces with thermo-responsive wettable nanograss are investigated for their boiling performances. It is found that the nanofilm coated surfaces show improved maximum heat transfer coefficient (HTCmax ) as well as critical heat flux (CHF) compared with the plain surface. The patterned surfaces shift the boiling curves to left, and the CHF increases with increasing nanograss cover density. The surfaces with thermo-responsive wettability, which responses to the external heating/cooling stimuli by gradually increasing or decreasing the wettability, show the most optimal CHF enhancement. This study serves as a proof-of-concept for efficient heat transfer through carefully fabricated nano-structured wettability-enhanced surfaces.